Pengembangan Aplikasi Pembelajaran Akuntansi Keuangan Berbantuan Flutterflow dengan Integrasi Artificial Intelligence - Fadil Muhammad; Roza Thohiri; Jufri Darma; Tuti Sriwedari; Choms Gary Ganda Tua Sibarani (LPPM Universitas Muhammadiyah Muara Bungo, 2026)
This study aims to develop an Android-based learning application called AiC: Accounting in Companion integrated with Gemini AI to assist vocational students in understanding Financial Accounting. The research method used was Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Research instruments included expert validation sheets, student response questionnaires, and learning outcome tests (pre-test and post-test). The research subjects consisted of 30 students from class XI AKL SMKN 7 Medan. The results showed a material feasibility level of 93% (Very Feasible) and a media feasibility level of 75% (Feasible). The practicality test by students obtained an average score of 91% (Very Practical). The effectiveness test using N-Gain analysis resulted in a score of 0.41, which falls into the Medium improvement category. The primary feature, AI-driven smart recommendations, successfully provided personalized guidance and automatic material navigation for students experiencing difficulties in quizzes. The conclusion of this study is that the AiC application is very feasible, practical, and effective as an innovative adaptive learning medium in the digital era.